Ultrasound Imaging for Stellate Ganglion Block: Direct Visualization of Puncture Site and Local Anesthetic Spread: A Pilot Study. Issue 4 (July 1995) - Kapral, Stephan; Krafft, Peter; Gosch, Max; Weinstabl, Christian; Fleischmann, Dominik
Abstract : Background and Objectives: Stellate ganglion block (SGB) inhibits sympathetic innervation and is a common treatment for reflex sympathetic dystrophy. During the positioning of the needle, there is a risk of injury to the adjacent structures. The aim of the study was to develop an ultrasonographic imaging technique for the performance of SGB. Methods: Twelve patients (ASA I-II) underwent SGB first by using the blind standard technique (group A: 8 mL bupivacaine 0.25%) and a second time by using an ultrasonographic imaging technique (group B: 5 mL bupivacaine 0.25%). In group B a 10 MHz ultrasound scanning probe was used to identify the anatomic structures and to guide the needle toward the transverse process of C6. Results: Stellate ganglion block was satisfactory in 11 of 12 attempts by the blind technique. Ultrasonographic guidance (group B) resulted in a complete block in all patients. Onset of block was observed within 10 minutes in only 10 of 12 group A patients, while all patients in group B exhibited an adequate block after 10 minutes. During the imaging technique, the needle was inserted to an average depth of 22 ± 3 mm and the injection of 5 mL bupivacaine resulted in an anesthetic depot with a mean diameter of 14 ± 3 mm. Distance from the depot to the vagal nerve was 5 ± 3 mm and 5 ± 4 mm to the root of C6. All patients (n = 4) with a distance of <1 mm between anesthetic depot and the root of C6 developed paresthesia within the corresponding cutaneous segment. Blind technique resulted in hematoma formation in three study patients, with no hematoma occurring during imaging technique. Conclusions: Ultrasonographic guided SGB may improve safety and allows the visualization of the local anesthetic depot. Studying the local anesthetic spread might allow the avoidance of side effects as well as typical complications of SGB.